Spekulationen an Devisenbörsen in der Zweiten Polnischen Republik. Vorbemerkungen [Speculation on foreign exchange markets in the Second Polish Republic. Preliminary remarks] - Macyra, Roman (Studia Historiae Oeconomicae, 2009)
The stock exchange is an integral part of the capital market, has an institutional character and a long tradition, and speculation is an "alternative" form of investing in it. The line between these terms was and remains very thin and is the subject of an ongoing dispute over definitions. It is precisely this state of uncertainty as to what is still an investment and what is not speculation, and the associated thrill between legal and illegal, permitted and legally prohibited, that has often been a path to wealth and its unimaginable increase, or the cause of bankruptcy. Although the fight against speculation has always been the concern of every official power, the words of a famous American businessman James R. Keene truthfully predicted the end result of this fight - "All life is speculation, man is born with the soul of a speculator."